Official methods for the determination of trans fat - Mossoba, Magdi M. (AOCS Press, 2009)
"This monograph describes the most common gas chromatographic and infrared spectroscopic official methods required for the determination of trans fatty acids for food labeling purposes. The authors review the current status and limitations of the latest methods and discuss the numerous factors that may have an impact on accuracy and precision. The extensive discussion informs current researchers and analysts in nutrition and food chemistry and technology and should provide a stimulus for improving trans fatty acid methodologies."--Publisher's description.
Keywords: Trans fatty acids -- Analysis.; Gas chromatography.; Infrared spectroscopy.; elektronické knihy; electronic books